Proposed layout improvement as factor for optimization of production process organizational - Gerlach, Gustavo; Bueno Da Silva, Vilmar; dos Santos, Lucas Almeida; do Amaral Adamy, Ana Paula; Garlet, Eliane (Revista de Administração da UFSM, 2017)
The current scenario of high competition makes companies look increasingly optimized processes, with the least possible losses and the ultimate in quality and productivity. Industrial layout plays an important role in this context, given that the physical layout of machinery, equipment, circulation areas, storage areas and people directly influences the efficiency of an operation. In the midst of this need for constant improvement, lean production emerged, which has proven to be an efficient method for companies to improve their performance. This study aims to define a layout that allows the optimization of business processes, based on the principles of lean production. The development of this research was carried out by the method of action research where analysis tools were used to diagnose the current situation and, thereafter, for the formulation of the proposed improvement. The results showed that the changes proposed in the layout are able to reduce the company's lead time by 46%, eliminate losses, improve the organization of productive sectors, and ensure agility in the manufacturing process.